Cardioprotection by ischemic postconditioning during surgical procedures. (August 2008) - Sadat, Umar; Walsh, Stewart R; Varty, Kevin
Acute myocardial ischemic insult remains the most prevalent cause of postoperative mortality and morbidity despite major advances in cardiovascular medicine. Preoperative cardiac assessment and optimization, intraoperative anesthetic techniques and perioperative medical prophylaxis are all used to minimize cardiac morbidity. Ischemic postconditioning is one of the latest techniques to be added to this regime of cardioprotection. Currently still in its infancy, this technique seems to provide valuable cardioprotection via a novel set of pathways. We present a literature review of published animal and human studies on ischemic postconditioning, focusing on the advances made in understanding this phenomenon since its inception and the relevant clinical applications.